Lack of Detachment, Affective Rumination or Problem-Solving Pondering? Decoding the Connection Between Job Insecurity and Exhaustion - Kathleen Otto; Emily Kleszewski (Scandinavian Journal of Work and Organizational Psychology, 2025)
While the maladaptive relationship between the threat of job loss and exhaustion is well established, little attention has been devoted to the cognitive and affective processes during non-work time that may occur in employees and may explain this relationship. Our study sought to open this black box and to fill its contents with knowledge from the fields of recovery research and perseverative thinking. We used three-wave data from a sample of 160 German employees with a 4-week interval between data assessments to examine the pathway from job insecurity to exhaustion. Potential mediators included lack of psychological detachment, affective rumination, and problem-solving pondering as facets of work-related rumination. Structural equation modeling, controlling for baseline levels of exhaustion at T1 as well as mediators at T1, provided evidence for a mediating role of affective rumination at T2 in the relationship between job insecurity at T1 and exhaustion at T3, suggesting that employees who perceive a higher threat of job loss ruminate after work, and ultimately show more exhaustion. The finding that this mechanism was observed while controlling for role ambiguity, workload, and unfinished tasks, underscores the relevance of job insecurity as a stressor. In contrast, neither detachment nor problem-solving pondering mediated the relationship between job insecurity and exhaustion, but did show relationships with the other assessed stressors. We discuss affective reactions to job insecurity as an important mechanism in explaining employees’ impaired well-being.